2005
DOI: 10.1074/jbc.m503150200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of FXYD10 (PLMS) with Na,K-ATPase from Shark Rectal Glands

Abstract: FXYD domain-containing proteins are tissue-specific regulators of the Na,K-ATPase that have been shown to have significant physiological implications. Information about the sites of interaction between some FXYD proteins and subunits of the Na,K-ATPase is beginning to emerge. We previously identified an FXYD protein in plasma membranes from shark rectal gland cells and demonstrated that this protein (FXYD10) modulates shark Na,K-ATPase activity. The present study was undertaken to identify the location of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…We have recently provided evidence for an interaction between the transmembrane segment of FYXD proteins and the ninth transmembrane segment of the ␣-subunit (22). A similar position of FXYD protein is supported by other approaches (31) while other locations have also been proposed recently (32). The role of the ninth transmembrane helix in Na ϩ transport and the close interaction between the transmembrane domain of FXYD proteins and the ninth transmembrane helix suggest that interaction between these transmembrane segments could be responsible for the functional effects of the association of these proteins with the ␣͞␤ complex, even if interactions between cytoplasmic domains may also affect Na,K-ATPase function.…”
Section: Discussionsupporting
confidence: 58%
“…We have recently provided evidence for an interaction between the transmembrane segment of FYXD proteins and the ninth transmembrane segment of the ␣-subunit (22). A similar position of FXYD protein is supported by other approaches (31) while other locations have also been proposed recently (32). The role of the ninth transmembrane helix in Na ϩ transport and the close interaction between the transmembrane domain of FXYD proteins and the ninth transmembrane helix suggest that interaction between these transmembrane segments could be responsible for the functional effects of the association of these proteins with the ␣͞␤ complex, even if interactions between cytoplasmic domains may also affect Na,K-ATPase function.…”
Section: Discussionsupporting
confidence: 58%
“…The first reported FXYD protein in fish was a phospholemman-like protein (i.e., FXYD10) from the piked dogfish ( Squalus acanthias ) [29]. Subsequent studies revealed the function of FXYD10 and its interaction with NKA [30], [31].…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 6A shows a model of the predicted spatial relationship between C1 and C2 and the ␣ 1 subunit derived from the crystal structure of shark rectal gland Na ϩ -K ϩ ATPase (7) and from cross-linking experiments (27). The model suggests that C2 comes into close proximity to basic amino acids of helix 4 of the ␣ subunit.…”
Section: Fxyd Proteins Reverse Namentioning
confidence: 99%